Interannual variation in nitrous oxide emissions from perennial ryegrass/white clover grassland used for dairy production - Burchill, William; Li, Dejun; Lanigan, Gary J; Williams, Micheal; Humphreys, James (Global change biology, 2014)
Nitrous oxide (N₂O) emissions are subject to intra‐ and interannual variation due to changes in weather and management. This creates significant uncertainties when quantifying estimates of annual N₂O emissions from grazed grasslands. Despite these uncertainties, the majority of studies are short‐term in nature (<1 year) and as a consequence, there is a lack of data on interannual variation in N₂O emissions. The objectives of this study were to (i) quantify annual N₂O emissions and (ii) assess the causes of interannual variation in emissions from grazed perennial ryegrass/white clover grassland. Nitrous oxide emissions were measured from fertilized and grazed perennial ryegrass/white clover grassland (WC) and from perennial ryegrass plots that were not grazed and did not receive N input (GB), over 4 years from 2008 to 2012 in Ireland (52°51′N, 08°21′W). The annual N₂O‐N emissions (kg ha⁻¹; mean ± SE) ranged from 4.4 ± 0.2 to 34.4 ± 5.5 from WC and from 1.7 ± 0.8 to 6.3 ± 1.2 from GB. Interannual variation in N₂O emissions was attributed to differences in annual rainfall, monthly (December) soil temperatures and variation in N input. Such substantial interannual variation in N₂O emissions highlights the need for long‐term studies of emissions from managed pastoral systems.